2019
DOI: 10.1186/s12909-019-1626-7
|View full text |Cite
|
Sign up to set email alerts
|

Combination of problem-based learning with high-fidelity simulation in CPR training improves short and long-term CPR skills: a randomised single blinded trial

Abstract: Background Performance of sufficient cardiopulmonary resuscitation (CPR) by medical personnel is critical to improve outcomes during cardiac arrest. It has however been shown that even health care professionals possess a lack of knowledge and skills in CPR performance. The optimal method for teaching CPR remains unclear, and data that compares traditional CPR instructional methods with newer modalities of CPR instruction are needed. We therefore conducted a single blinded, randomised study involvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
17

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(78 citation statements)
references
References 36 publications
1
60
0
17
Order By: Relevance
“…Students reported better knowledge through the highfidelity simulation teaching intervention compared to traditional clinical settings over time. Students in the HFS intervention group had better performance and had increased knowledge and performance 10,11 compared to the control group. These differences showed that the HFS-DKA had contributed to improving knowledge and critical thinking in the simulation group.…”
Section: Discussionmentioning
confidence: 93%
“…Students reported better knowledge through the highfidelity simulation teaching intervention compared to traditional clinical settings over time. Students in the HFS intervention group had better performance and had increased knowledge and performance 10,11 compared to the control group. These differences showed that the HFS-DKA had contributed to improving knowledge and critical thinking in the simulation group.…”
Section: Discussionmentioning
confidence: 93%
“…Após a criação de um manequim infantil para treinamento em SBV, notou-se melhoria significativa no atendimento inicial à vítima, proporção correta de compressões torácicas e profundidade, frequência respiratória adequada e acionamento de suporte médico em tempo hábil. Essa intervenção de baixo custo apresentou potencial para ampla aplicação em países desenvolvidos e em desenvolvimento [16][17][18] .…”
Section: Discussionunclassified
“…to <15, moderate quality; and ≥15, high quality (21) . (13) *CINAHL = Cumulative Index to Nursing and Allied Health Literature; † LILACS = Latin American and Caribbean Literature in Health Sciences; ‡ CPR = Cardiopulmonary resuscitation Figure 1 -Flowchart of the identification, selection and inclusion process of studies adapted from the Preferred Reporting Items for Systematic Review and Meta-Analyzes (PRISMA).…”
Section: Thus the Following Guiding Question Was Structuredmentioning
confidence: 99%